2011
DOI: 10.1089/jmf.2010.0284
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Chemicals from Carrot (Daucus carota) Juice Extracts for the Treatment of Leukemia

Abstract: Overwhelming evidence indicates that consumption of fruits and vegetables with antioxidant properties correlates with reduced risk for cancers, including leukemia. Carrots contain beneficial agents, such as β-carotene and polyacetylenes, which could be effective in the treatment of leukemia. This study investigated the effect of carrot juice extracts on myeloid and lymphoid leukemia cell lines together with normal hematopoietic stem cells. Leukemia cell lines and nontumor control cells were treated with carrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…Treatment of leukemia cell lines with carrot juice extract induced apoptosis and caused cell cycle arrest. Lymphoid cell lines were affected to a greater extent than were myeloid cell lines, while, normal hematopoietic stem cells were less sensitive than cancer cell lines [106]. The anticancer effect of Daucus carota oil extract fractions was studied on the human breast adenocarcinoma cell lines MDA-MB-231 and MCF-7.…”
Section: Pharmacological Effects: Cytotoxic Effectsmentioning
confidence: 99%
“…Treatment of leukemia cell lines with carrot juice extract induced apoptosis and caused cell cycle arrest. Lymphoid cell lines were affected to a greater extent than were myeloid cell lines, while, normal hematopoietic stem cells were less sensitive than cancer cell lines [106]. The anticancer effect of Daucus carota oil extract fractions was studied on the human breast adenocarcinoma cell lines MDA-MB-231 and MCF-7.…”
Section: Pharmacological Effects: Cytotoxic Effectsmentioning
confidence: 99%
“…At the same time, the root extract of Beta vulgaris L. (Chenopodiaceae) (beet) can inhibit the growth of hormone-dependent human breast cancer cells (Tripathy & Pradhan, 2013) and taproot juice of Daucus sativus Hort. Ex Passerini (Apiaceae) (carrot) may be an excellent source of bioactive chemicals for the treatment of different leukemias affecting somewhat stronger lymphoid than myeloid malignancies (Zaini et al, 2011(Zaini et al, , 2012.…”
Section: Vegetables and Fruitsmentioning
confidence: 99%
“…Falcarinol, a natural polyacetylene from carrots (Daucus carota) has been previously indicated as an inducer of apoptosis and inhibitor of cellular proliferation within Leukaemia cell lines [4,5]. The key potential for natural agents in anti-cancer therapies is in the combination with existing chemotherapy and anti-tumour agents.…”
Section: Discussionmentioning
confidence: 99%
“…Three human lymphoid Leukaemia cell lines were used in this study, which we have previously shown have high sensitivity to Falcarinol [5], CCRF-CEM (acute lymphoblastic Leukaemia) (ATCC: CCL-119, Middlesex, UK); Jurkat (peripheral blood T cell Leukaemia) (ATCC: TIB-152, Middlesex, UK); and MOLT-3 (acute lymphoblastic Leukaemia patient relapsed following chemotherapy) (ATCC: CRL-1552, Middlesex, UK) [5]. All cell lines used in this study were routinely tested against mycoplasma bacterial infection using the MycoAlert® Mycoplasma Detection Kit (Lonza, USA).…”
Section: Cell Culturementioning
confidence: 99%